Role of Extracellular Vesicles in Placental Inflammation and Local Immune Balance - Zengfang Wang; Ruizhen Yang; Jiaojiao Zhang; Pingping Wang; Zengyan Wang; Jian Gao; Xue Liu (Mediators of Inflammation)
Background. Pregnancy maintenance depends on the formation of normal placentas accompanied by trophoblast invasion and vascular remodeling. Various types of cells, such as trophoblasts, endothelial cells, immune cells, mesenchymal stem cells (MSCs), and adipocytes, mediate cell-to-cell interactions through soluble factors to maintain normal placental development. Extracellular vesicles (EVs) are diverse nanosized to microsized membrane-bound particles released from various cells. EVs contain tens to thousands of different RNA, proteins, small molecules, DNA fragments, and bioactive lipids. EV-derived microRNAs (miRNAs) and proteins regulate inflammation and trophoblast invasion in the placental microenvironment. Maternal-fetal communication through EV can regulate the key signaling pathways involved in pregnancy maintenance, from implantation to immune regulation. Therefore, EVs and the encapsulating factors play important roles in pregnancy, some of which might be potential biomarkers. Conclusion. In this review, we have summarized published studies about the EVs in the placentation and pregnancy-related diseases. By summarizing the role of EVs and their delivering active molecules in pregnancy-related diseases, it provides novel insight into the diagnosis and treatment of diseases.